2019
DOI: 10.1039/c8ra09274e
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ethylene oxide)/Ag ions and nanoparticles/1-hexyl-3-methylimidazolium tetrafluoroborate composite membranes with long-term stability for olefin/paraffin separation

Abstract: A poly(ethylene oxide)(PEO)/AgBF4/1-hexyl-3-methylimidazolium tetrafluoroborate (HMIM+BF4−) composite membrane with long-term stability was prepared for olefin/paraffin separation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…The obtained results showed that thermal stability of the fabricated MMMs undergoes a decline as the NH 2 ‐HNTs are incorporated into the polymer body compared to NM. Penetration of the embedded HNTs among the polymer chains and accordingly increase of FFV of the MMMs can be the principal reason why the MMMs have lower thermal stability than the NM 48–50 . It is noteworthy that all the resultant membranes' thermal resistances are great enough for the permeation measurements at ordinary operating temperatures 4 …”
Section: Resultsmentioning
confidence: 99%
“…The obtained results showed that thermal stability of the fabricated MMMs undergoes a decline as the NH 2 ‐HNTs are incorporated into the polymer body compared to NM. Penetration of the embedded HNTs among the polymer chains and accordingly increase of FFV of the MMMs can be the principal reason why the MMMs have lower thermal stability than the NM 48–50 . It is noteworthy that all the resultant membranes' thermal resistances are great enough for the permeation measurements at ordinary operating temperatures 4 …”
Section: Resultsmentioning
confidence: 99%
“…The double bond in olefins interacts with certain metals, [15–18] including silver ions [19–21] . Consequently, silver ions (Ag + ) have been extensively investigated as olefin carriers in both membrane and absorption‐based olefin/paraffin separation processes [19–31] . However, membranes containing silver ions have never been deployed commercially due, in part, to their sensitivity to even trace levels of hydrogen gas, which reduces silver ions to silver metal, which is generally nonselective for binding olefins [20, 21, 26] .…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Consequently, silver ions (Ag + ) have been extensively investigated as olefin carriers in both membrane and absorption-based olefin/paraffin separation processes. [19][20][21][22][23][24][25][26][27][28][29][30][31] However, membranes containing silver ions have never been deployed commercially due, in part, to their sensitivity to even trace levels of hydrogen gas, which reduces silver ions to silver metal, which is generally nonselective for binding olefins. [20,21,26] The deactivation of silver ions results in membrane selectivity loss and yields silver metal nanoparticles that were not active for olefin binding.…”
Section: Introductionmentioning
confidence: 99%
“…Silver ions can be reversibly reacted with olefin molecules, forming a silver-olefin complex [1][2][3][4][5][6][7][8][9]. Thus, the silver polymer electrolytes have been investigated as an alternative method in the distillation process, requiring high cost and space [2,4].…”
Section: Introductionmentioning
confidence: 99%